2020
DOI: 10.3390/v12091039
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Antiviral Immune Response and Its Circumvention by Coronaviruses

Abstract: Some coronaviruses are zoonotic viruses of human and veterinary medical importance. The novel coronavirus, severe acute respiratory symptoms coronavirus 2 (SARS-CoV-2), associated with the current global pandemic, is characterized by pneumonia, lymphopenia, and a cytokine storm in humans that has caused catastrophic impacts on public health worldwide. Coronaviruses are known for their ability to evade innate immune surveillance exerted by the host during the early phase of infection. It is important to compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 141 publications
(162 reference statements)
0
10
0
Order By: Relevance
“…Cumulative pieces of evidence have also shown that paramyxoviruses, some flaviviruses [for example, Dengue Virus (DENV) and West Nile Virus (WNV)], and reoviruses, may be sensed by both RIG-I and MDA5 (Kawai and Akira, 2010;Goubau et al, 2013;Chan and Gack, 2016;Morgan Brisse, 2019). Well-known viral pathogens responsible for acute respiratory infections, such as SARS-CoV, SARS-CoV-2, and MERS-CoV are detected by endosomal PRRs, including TLR3 and 7, and/or cytoplasmic sensors, such as RIG-I and MDA5 (Felsenstein et al, 2020;Liu et al, 2020). NOD-like receptors (NLRs) are a large family of intracellular PRRs.…”
Section: Innate Immunity Innate Detection Of Viral Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cumulative pieces of evidence have also shown that paramyxoviruses, some flaviviruses [for example, Dengue Virus (DENV) and West Nile Virus (WNV)], and reoviruses, may be sensed by both RIG-I and MDA5 (Kawai and Akira, 2010;Goubau et al, 2013;Chan and Gack, 2016;Morgan Brisse, 2019). Well-known viral pathogens responsible for acute respiratory infections, such as SARS-CoV, SARS-CoV-2, and MERS-CoV are detected by endosomal PRRs, including TLR3 and 7, and/or cytoplasmic sensors, such as RIG-I and MDA5 (Felsenstein et al, 2020;Liu et al, 2020). NOD-like receptors (NLRs) are a large family of intracellular PRRs.…”
Section: Innate Immunity Innate Detection Of Viral Infectionsmentioning
confidence: 99%
“…Innate immune signaling is initiated by sensing specific viral components, called pathogen associate molecular patterns (PAMPs), such as viral dsRNA, ssRNA, DNA, transcription products, and other viral components including replication intermediates. The sense of PAMPs by PRRs leads to the activation of downstream molecules including mitochondrial antiviral signaling protein (MAVS), stimulator of IFN genes (STING) or MYD88, and transcription factors, such as interferon regulatory factors (IRF3/5/7), NF-kB, AP1, and so forth (Koyama et al, 2008;Ishikawa et al, 2009;Kawai and Akira, 2010;Rathinam and Fitzgerald, 2011;Jensen and Thomsen, 2012;Goubau et al, 2013;Lazear et al, 2013;Iwasaki and Pillai, 2014;Goraya et al, 2015;Chan and Gack, 2016;Shrivastava et al, 2016;Chen et al, 2018;Ma et al, 2018;Chiang and Liu, 2019;Morgan Brisse, 2019;Felsenstein et al, 2020;Liu et al, 2020). The PRR-mediated signaling pathways ultimately lead to the secretion of numerous antiviral molecules, including type I and type III IFNs, and other pro-inflammatory cytokines and chemokines (Koyama et al, 2008;Ishikawa et al, 2009;Kawai and Akira, 2010;Rathinam and Fitzgerald, 2011;Jensen and Thomsen, 2012;Goubau et al, 2013;Lazear et al, 2013;Iwasaki and Pillai, 2014;Goraya et al, 2015;Chan and Gack, 2016;Shrivastava et al, 2016;Chen et al, 2018;Ma et al, 2018;Chiang and Liu, 2019;Morgan Brisse, 2019;Felsenstein et al, 2020;…”
Section: Innate Immune Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that the SARS-CoV-2 nsp16 and nsp10 complex can carry out the 5′ cap Nm on virally encoded mRNAs to mimic cellular mRNAs, thus protecting the virus from host innate immune restriction [ 327 ]. This may provide a potential strategy to develop coronavirus vaccines and antiviral drugs [ 328 ].…”
Section: Implications Of Rna Epigenetics In Human Diseasesmentioning
confidence: 99%
“…Stoddard et al [ 3 ] described an ensemble molecular docking approach and proposed a designed guideline to virtually trial potential drug candidates to the SARS-CoV-2 main protease. Liu et al [ 4 ] reviewed several aspects of antiviral immune response and evasion mechanisms presented by coronaviruses that have caused epidemic diseases in humans and domestic animals. The discussed mechanisms included the hijack of antigen-presenting cells to virus dissemination through mucosal tissues; escape from RNA sensors by shielding RNA intermediates in replication organelles and 2′-O-methylation modification of virus RNA; antagonization of interferon-mediated signal transduction, and inhibition of interferon stimulated genes (ISG).…”
mentioning
confidence: 99%